APC/C ubiquitin ligase: Functions and mechanisms in tumorigenesis. (December 2020) - Schrock, Morgan S.; Stromberg, Benjamin R.; Scarberry, Luke; Summers, Matthew K.
Abstract: The anaphase promoting complex/ cyclosome (APC/C), is an evolutionarily conserved protein complex essential for cellular division due to its role in regulating the mitotic transition from metaphase to anaphase. In this review, we highlight recent work that has shed light on our understanding of the role of APC/C coactivators, Cdh1 and Cdc20, in cancer initiation and development. We summarize the current state of knowledge regarding APC/C structure and function, as well as the distinct ways Cdh1 and Cdc20 are dysregulated in human cancer. We also discuss APC/C inhibitors, novel approaches for targeting the APC/C as a cancer therapy, and areas for future work.